Scaling impact, enriching lives: HarvestPlus 2024 annual report - HarvestPlus (International Food Policy Research Institute, 2025)
In 2024, the Global South continued to face food and nutrition insecurity driven by conflict, economic shocks, forced displacement, and climate extremes. Malnutrition persists at high levels, especially among children, while funding for solutions is declining. A fundamental rethink is needed about how to sustainably meet the food and nutrition needs of vulnerable populations. At HarvestPlus, we are acting urgently to scale up nutrients in diets in Asia, Africa, and South America. By the end of 2024, over 360 million people benefited from more nutritious diets through biofortified foods—a nine percent increase over last year. There is an additional reach of biofortified crops through organizations like International Potato Center (CIP), The Alliance of Bioversity International and CIAT, IITA, and others civil society actors which is heartening to note. We continued to empower women smallholder farmers along the value chain with knowledge, business skills, and opportunities. They are driving change by developing and marketing nutrientenriched foods within their communities, making their local food systems more resilient. Improving the nutrition of children and adolescents is a vital focus of our work. This year, we strengthened local supply chains and facilitated the inclusion of home-grown nutritious crops in school meal programs. As a result, over one million schoolchildren in Asia and Africa had access to meals enriched with biofortified foods. These efforts, combined with our delivery of nutrition education, are shaping healthier, more productive futures. A special thank you to Chef Sanjeev Kapoor for championing this work in India under our Nutri-Pathshala school meal model. Partnerships with CGIAR centers and national agricultural research and extension systems (NARES) enabled the release of 12 new biofortified crop varieties in five countries in 2024. These varieties provide farmers with competitive yields and more nutrients—adding diversity to the agricultural system while enriching the food system. By boosting supply and demand, we are making nutrient-rich foods more affordable, available, and accessible for the most vulnerable. Our delivery models scale innovations like biofortification and other nutritious crops and technologies rapidly and at low cost, ensuring they reach those who need them most and create impact at scale. In Pakistan, over 50 percent of wheat grain production is now zinc-enriched, funded primarily through public and private seed sector investments. In Nigeria, over 10 million people are consuming vitamin A maize on farms, with the private sector playing a major role in its scaleup. Going forward, these delivery models will be deployed through our scaling arm, HarvestPlus Solutions. We are encouraged by strong interest from the private sector in partnering with HarvestPlus Solutions. These partnerships are central to our long-term development work, particularly in the current funding environment. In 2024, we continued to transition HarvestPlus’ delivery and commercialization work to HarvestPlus Solutions and its network of partners. Sustainability is at the core of our approach, where local actors lead local solutions at the last mile. Our progress in 2024 is thanks to the collective dedication and passion of our team, partners, and donors. We have come a long way, but there’s still more to do. With continued support, we can deepen our impact, accelerate innovation, and nourish millions more.